PENGARUH ARUS DAN WAKTU TERHADAP LAPISAN ZINC PLATING PADA MATERIAL SGD400-D DENGAN MENGGUNAKAN PROSES ELEKTROPLATING - Ari Setiawan; Novi Laura Indrayani; Budi Herawan (Jurnal Ilmiah Teknik Mesin, 2019)
This research was conducted to find the ideal current and time used during the plating process, because in every industry the most frequent problems are the thickness that coats the material and the corrosion rate of the material that causes the material to become damaged or no good. This study uses SGD400 carbon steel and zinc as a coating. The research was carried out on a tank containing various kinds of chemical liquids and using electric current as conductivity for the coating media. Analysis using layer thickness measurement using vernier caliper measuring instrument and weight loss method. The results obtained from searching the current and the ideal time using a current of 900 A and a time of 60 minutes is 0.015 mm or 15 μm thick and the SST test (Salt Spray Test) at 72 hours No White Rust and 168 Hours No Red Rust. And good coating results can be seen in microstructure testing using keyence microscope media